Case Study Of Nestle(Malaysia) Berhad "Creting Values Through Branding" - Nik Ahmad, Nik Faizal (2007)
This thesis encompasses the food and beverages industry of Malaysia whilst Nestle Malaysia Berhad standing at the specific subject to be focused on. The thesis clings on the environment and situation that Nestle Malaysia Berhad is facing and challenges it were to undertake to compete in the industry in order to reclaim its domestic dominance and to enhance its global presence.